Unanticipated discovery: basal metabolic rate as an independent risk factor for metabolic dysfunction-associated steatotic liver disease in a 5-year longitudinal cohort study of non-obese individuals in China - Luo, Jian; Gong, Danfeng; Guo, Min; Cheng, Long; Wu, Xueyan (Frontiers in Medicine, 2025)
ObjectiveThe role of basal metabolic rate (BMR) in Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) remains controversial, with previous studies yielding inconsistent results. The precise relationship remains poorly understood, particularly in non-obese individuals. This study aimed to investigate the longitudinal association between BMR and incident MASLD in a large, non-obese Chinese cohort.MethodsThis longitudinal cohort study included 16,173 non-obese participants free of MASLD at baseline. They were prospectively followed up for 5 years, with the outcome event being the development of MASLD. Participants were divided into quartiles based on their basal metabolic rate (BMR). The association between BMR and incident MASLD was examined using both Cox regression models and restricted cubic spline analysis (RCS).ResultsDuring the 5-year follow-up period, 2,322 non-obese participants developed MASLD. Multivariate Cox regression analysis revealed that after fully adjusting for relevant confounding factors, the BMR was positively associated with incident MASLD, and the risk of MASLD gradually increased with increasing BMR (HR: 1.3, 95% CI: 1.3, 1.4; p for trend < 0.0001). Using RCS regression, we found a positive linear correlation between the BMR and the risk of incident MASLD. Stratified analysis revealed an association between the BMR and increased incidence of MASLD in all the subgroups. Additionally, significant interactions were found between BMR and sex, systolic blood pressure (SBP), uric acid (UA), creatinine (CR), and triglycerides (TGs) (p for interaction < 0.05). Mediation analysis indicated that insulin resistance mediated 5.16% of the effect of the BMR on incident MASLD.ConclusionIn this non-obese Chinese cohort, an elevated BMR was identified as an independent risk factor for incident MASLD. This suggests that BMR could be a valuable early biomarker for MASLD risk stratification, even in individuals without obesity.